Chinese Herbal Medicine and Salmeterol and Fluticasone Propionate for Chronic Obstructive Pulmonary Disease: Systematic Review and Network Meta-Analysis. Issue 20 (May 2016) - Chung, Vincent C.H.; Wu, Xinyin; Ma, Polly H.X.; Ho, Robin S.T.; Poon, Simon K.; Hui, David S.; Wong, Samuel Y.S.; Wu, Justin C.Y.
Abstract : Abstract: Among Chinese populations worldwide, Chinese herbal medicines (CHMs) are often used as an adjunct to pharmacotherapy in managing chronic obstructive pulmonary disease (COPD). However, the relative performance among different CHM is unknown. The aim of this study was to evaluate comparative effectiveness of different CHM when used with salmeterol and fluticasone propionate (SFP), compared with SFP alone. This study is a systematic review of randomized controlled trials (RCTs) with network meta-analyses (NMAs). Eight electronic databases were searched. Data from RCTs were extracted for random effect pairwise meta-analyses. Pooled relative risk (RR) with 95% confidence interval (CI) was used to quantify the impact of CHM and SFP on forced expiratory volume in 1 second (FEV1 ), St George's Respiratory Questionnaire (SGRQ) scoring, and 6-Minute Walk Test (6MWT). NMA was used to explore the most effective CHM when used with SFP. Eleven RCTs (n = 925) assessing 11 different CHM were included. Result from pairwise meta-analyses indicated favorable, clinically relevant benefit of CHM and SFP on FEV1 [7 studies, pooled weighted mean difference (WMD) = 0.20 L, 95% CI: 0.06–0.34 L], SGRQ scoring (5 studies, pooled WMD = −4.99, 95% CI: −7.73 to −2.24), and 6MWT (3 studies, pooled WMD = 32.84 m, 95% CI: 18.26–47.42). Results from NMA showed no differences on the comparative effectiveness among CHM formulations for improving FEV1 . For SGRQ, NMA suggested that Runfeijianpibushen decoction and Renshenbufei pills performed best. Use of CHM on top of SFP can provide clinically relevant benefit for COPD patients on FEV1 and SGRQ. Additional use of Runfeijianpibushen decoction and Renshenbufei pills showed better effect on improving SGRQ. Use of CHM and SFP may provide clinically relevant benefit for COPD patients on FEV1, SGRQ, and 6MWT. Use of different CHM formulae included in this NMA showed similar effect for increasing FEV1, while the additional use of Runfeijianpibushen formula and Renshenbufei Pills showed better effect on improving SGRQ. Well conducted, adequately powered trials are needed to confirm their effectiveness in the future.